HEPATOPROTECTIVE ACTIVITY OF COMBINATION OF PHYLLANTHUS NIRURI AND CURCUMA LONGA EXTRACTS AGAINST ETHANOL INDUCED TOXICITY IN WISTAR RATS - VINAY BS; SHALINI ADIGA; SHOBHA KAMATH; MOHANDAS RAO KG; AVIN S (International Journal of Pharma and Bio Sciences, 2016)
Alcohol is an important substance with addictive potential. Alcohol is metabolised in the liver. Free radicals generated during the metabolism of alcohol is responsible for hepatic damage. Options available for treatment of alcohol induced liver disease was inadequate in modern medicine. Phyllanthus niruri and Curcuma longa have been shown to have hepatoprotective activity. Hence this study was undertaken to evaluate the effects of Phyllanthus niruri and Curcuma longa in combination to prevent alcohol induced hepatotoxicity. Evaluation was done by comapring the levels of liver enzymes, bilirubin, antioxidants, thiopentone induced sleeping time and liver hisotpathology in various groups of albino rats after administration of ethanol. Treatment with extracts of Phyllanthus niruri and Curcuma longa caused a significant reduction in liver enzymes, bilirubin levels and increase in antioxidants. The results of our study indicate that combination of Phyllanthus niruri and Curcuma longa possess significant hepatoprotective activity against alcohol induced liver damage.